Spatial Distribution of Nitrogen on Grazed Karst Landscapes - Douglas G. Boyer; Ghiath A. Alloush (The Scientific World Journal)
The impact on water quality by agricultural activity in karst terrain is an important consideration for resource management within the Appalachian region. Karst areas comprise about 18% of the region’s land area. An estimated one-third of the region’s farms, cattle, and agricultural market value are located on karst terrain. Mean nitrate concentrations in several karst springs in southeastern West Virginia exhibit a strong linear relationship with the percentage of agriculture land cover. Development of best management practices for efficient nitrogen (N) use and reduction of outflow of N to water from karst areas requires knowledge about N dynamics on those landscapes. Water extractable NO3-N and NH4-N were measured along transects at four soil depths in two grazed sinkholes and one wooded sinkhole. Distribution of soil NO3-N and NH4-N were related to frequency of animal presence and to topographic and hydrologic redistribution of soil and fecal matter in the grazed sinkholes. Karst pastures are characterized by under drainage and funneling of water and contaminants to the shallow aquifer. Control of NO3-N leaching from karst pasture may depend on management strategies that change livestock grazing behavior in sinkholes and reduce the opportunity for water and contaminants to quickly reach sinkhole drains.